Gun Control: State Versus Federal Regulation of Firearms - Harwood, William (Maine Policy Review, 2002)
William Harwood addresses the complex question of whether gun control should be regulated by the federal or state government, or by some combination of both. In a thorough look at the history of federal and Maine state gun control—and at the various ways the issue of gun violence can be framed—Harwood concludes that neither level of government has a clear mandate to regulate exclusively. Rather, he argues for a more cooperative federal-state approach that allows the federal government to apply uniform regulations when appropriate and the states to experiment with further regulations if so desired.
Keywords: Maine; gun control; federal gun control; second amendment